PENDAMPINGAN PENINGKATAN DAYA SAING DAN LEGALITAS UMKM DHANY BAKERY DI JOMBANG DALAM MENDUKUNG PENCAPAIAN SDGs - Setyawati, Ira; Agustin, Resty; Winarno, Agung; Hermawan, Agus (Penerbit Widina, Widina Media Utama, 2025)
This community service activity aims to improve the competitiveness, business legality, and management quality of Dhany Bakery, a micro, small, and medium enterprise (MSME) located in Jogoroto District, Jombang Regency. The assistance was provided by 2024–2025 Master of Management students from Malang State University (UM), namely Ira Setyawati and Resty Agustin, under the guidance of Prof. Dr. Agung Winarno, M.M. and Dr. Agus Hermawan, GradDipMgt., M.Si., M.Buss. The activities included assistance with business licensing, trademark intellectual property rights (IPR) registration, preparation of simple financial reports, and training in digital marketing and branding strategies. The implementation method used a participatory approach with a combination of observation, training, and intensive mentoring. The results of the assistance showed an increase in business actors' understanding of the importance of legality, financial recording, and digital marketing. This is evidenced by the marketing of products through WhatsApp Business, Instagram, and GoFood. Additionally, this program supports the achievement of the SDGs, particularly SDG 1, SDG 8, and SDG 9. Overall, the assistance has strengthened the managerial foundation of Dhany Bakery while boosting the business owner's confidence in developing the business.ABSTRAKKegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan daya saing, legalitas usaha, dan kualitas manajemen UMKM Dhany Bakery yang berlokasi di Kecamatan Jogoroto, Kabupaten Jombang. Pendampingan dilakukan oleh mahasiswa Magister Manajemen Universitas Negeri Malang (UM) angkatan 2024–2025, yakni Ira Setyawati dan Resty Agustin, dengan bimbingan Prof. Dr. Agung Winarno, M.M. dan Dr. Agus Hermawan, GradDipMgt., M.Si., M.Buss. Kegiatan meliputi pendampingan perizinan usaha, pendaftaran Hak Kekayaan Intelektual (HKI) merek dagang, penyusunan laporan keuangan sederhana, serta pelatihan strategi pemasaran digital dan branding. Metode pelaksanaan menggunakan pendekatan partisipatif dengan kombinasi observasi, pelatihan, dan mentoring intensif. Hasil pendampingan menunjukkan peningkatan pemahaman pelaku usaha terhadap pentingnya legalitas, pencatatan keuangan, serta pemasaran digital. Hal ini ditunjukkan dengan adanya pemasaran produk melalui WhatsApp bisnis, Instagram dan Gofood. Selain itu, program ini juga mendukung pencapaian SDGs, khususnya SDG 1, SDG 8, dan SDG 9. Secara keseluruhan, pendampingan mampu memperkuat fondasi manajerial Dhany Bakery sekaligus meningkatkan kepercayaan diri pemilik usaha dalam mengembangkan bisnis.